2003
DOI: 10.1080/08897070309511552
|View full text |Cite
|
Sign up to set email alerts
|

Condom Use Behaviors in HIV–Infected African American Crack Cocaine Users

Abstract: The purpose of this study was to investigate sexual risk behaviors and factors associated with consistent condom use of HIV+ African Americans receiving HAART who smoke crack. Participants were African Americans in Houston, Texas and over 18, being treated for HIV, and reported currently using crack. Measures included demographic variables, sexual behaviors, drug use, and nine psychosocial scales and seven escape scales. One hundred thirty seven participated in the study. Condom use was low across all partner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…A esse respeito, nos Estados Unidos, Perlman et al 7,8 identificaram o shotgun, uma estratégia de uso que, embora encarada como o compartilhamento inocente de crack (e outras drogas fumáveis) entre dois usuários, tem propiciado contextos eróticos de uso, aumentando a incidência de encontros homo e heterossexuais. Como na cultura de crack o uso de preservativos é geralmente inconsistente 9 , esses encontros podem facilitar a transmissão de HIV e outras doenças sexualmente transmissíveis (DSTs). Como os principais aspectos das culturas de crack brasileira e norte-americana têm caminhado pari passu, sugere-se que essa técnica, entre outras de riscos semelhantes, já exista em contexto brasileiro, embora não tenha sido formalmente identificada.…”
Section: Introductionunclassified
“…A esse respeito, nos Estados Unidos, Perlman et al 7,8 identificaram o shotgun, uma estratégia de uso que, embora encarada como o compartilhamento inocente de crack (e outras drogas fumáveis) entre dois usuários, tem propiciado contextos eróticos de uso, aumentando a incidência de encontros homo e heterossexuais. Como na cultura de crack o uso de preservativos é geralmente inconsistente 9 , esses encontros podem facilitar a transmissão de HIV e outras doenças sexualmente transmissíveis (DSTs). Como os principais aspectos das culturas de crack brasileira e norte-americana têm caminhado pari passu, sugere-se que essa técnica, entre outras de riscos semelhantes, já exista em contexto brasileiro, embora não tenha sido formalmente identificada.…”
Section: Introductionunclassified
“…However, some studies have shown that HIV-positive drug users show resistance to reduce high-risk behaviors. This may be due to social pressure, poverty, unemployment, low educational level, substance dependence, and clients' preferences (9). Little investigation has been conducted on the effect of HIVpositive awareness on the modification of risk behaviors among female HIV-positive drug-users.…”
Section: Introductionmentioning
confidence: 99%
“…This is also the case with African-Americans whose STD-and HIV-risks are especially high (Brunswick & Flory, 1998;Edlin et al, 1992;Riehmann et al, 1998;Ross, Timpson, Williams, & Bowen, 2003b;Timpson et al, 2001;Wingood & DiClemente, 1998). African-American crack cocaine users exchange sex for drugs and/or money, have sex with multiple concurrent partners, use condoms inconsistently, and have more sex partners than non-crack cocaine users (Calsyn, Meinecke, Saxon, & Stanton, 1992;Desenclos, Papaevangelou, & Ancelle-Park, 1993;Hershberger, Wood, & Fisher, 2003;Ross, Kohler, Grimley, & Bellis, 2003a;Timpson, Williams, Bowen, & Keel, 2003;Williams et al, 2000). Several theoretical models of behavior change, such as the Theory of Planned Behavior (Ajzen, 1991), social cognitive theory (Bandura, 1986), the Health Belief Model (Becker & Joseph, 1988), an AIDS-risk model (Catania, Kegeles, & Coates, 1990), and the transtheoretical model (Prochaska & DiClemente, 1984, 1986 have been used to explain condom use behavior.…”
Section: Introductionmentioning
confidence: 99%